DIURNAL VARIATION OF HAEMOSTATIC RESPONSE TO EXERCISE IN YOUNG SEDENTARY MALES - Marefat Siahkouhian; Davar Khodadadi; Lotfali Bolboli (Termedia Publishing House, 2013)
The aim of this study was to evaluate diurnal variations in the haemostatic response to submaximal exercise performed by young, sedentary men. Fifteen healthy young sedentary males aged 25.6 ± 1.34 (mean ± SD) years performed two exercise sessions, morning and evening, at 700of maximal oxygen consumption (VO2max) on a cycle ergometer for 30 min. Platelet count (PC), activated partial thromboplastin time (aPTT), prothrombin time (PT), fibrinogen, tissue plasminogen activator (tPA) and plasminogen activator inhibitor-1 (PAI-1) activity were measured as dependent variables. Exercise produced significant increases in PC and fibrinogen for both sessions (P≤0.05), which returned to the resting values after recovery only in the evening session. APTT and PT shortened immediately after exercise, which remained after recovery for both sessions (P≤0.01). Exercise presented significant increases in tPA activity (P≤0.001), which returned to the baseline after recovery in both exercises. PAI-1 activity was significantly higher during the morning than evening (P≤0.05), but no longer demonstrated exercise-related changes. It was found that exercise caused activation of both coagulation and fibrinolysis processes, partly related to the time of the day when the exercise was performed.